1995
DOI: 10.1161/01.cir.91.1.215
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin Improves Vital Organ Blood Flow During Closed-Chest Cardiopulmonary Resuscitation in Pigs

Abstract: We conclude that administration of vasopressin leads to a significantly higher coronary perfusion pressure and myocardial blood flow than epinephrine during closed-chest CPR in a pig model of ventricular fibrillation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
85
1
8

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 284 publications
(96 citation statements)
references
References 23 publications
2
85
1
8
Order By: Relevance
“…As an alternative therapy, Morales et al (1999) reported a set of canine experiments where vasopressin levels showed a marked increase at the onset of blood loss followed by a fall to well below the normal physiological level. Voelckel et al (2000) and Lindner et al (1995) demonstrated that the administration of vasopressin improved the survival rate in porcine cases and more recently Krismer et al (2005) reported for human as well. Excessive doses of vasopressin however have been known to induce injuries to the gastrointestinal tract, skin, myocardium and liver (Malay et al 2004;Yoo et al 2007).…”
Section: Introductionmentioning
confidence: 80%
“…As an alternative therapy, Morales et al (1999) reported a set of canine experiments where vasopressin levels showed a marked increase at the onset of blood loss followed by a fall to well below the normal physiological level. Voelckel et al (2000) and Lindner et al (1995) demonstrated that the administration of vasopressin improved the survival rate in porcine cases and more recently Krismer et al (2005) reported for human as well. Excessive doses of vasopressin however have been known to induce injuries to the gastrointestinal tract, skin, myocardium and liver (Malay et al 2004;Yoo et al 2007).…”
Section: Introductionmentioning
confidence: 80%
“…During ventricular fibrillation, doseresponse investigations of three vasopressin doses (0.2, 0.4, and 0.8 units/kg) compared with the maximum effective dose of 200 g/kg epinephrine showed that 0.8 units/kg vasopressin was the most effective drug for increasing vital organ blood flow (2). Also, vasopressin significantly improved cerebral oxygen delivery and the ventricular fibrillation mean frequency during CPR when compared with a maximum dose of epinephrine (3).…”
Section: Arginine Vasopressin During Cpr In Laboratory Modelsmentioning
confidence: 97%
“…Unter diesen Gesichtspunkten wĂŒrde Adrenalin heute fĂŒr die Therapie bei einer CPR nicht mehr zugelassen werden; vielmehr genießt es lediglich eine Art "Verbleiberecht" aufgrund der historischen Tradition, was die Amerikaner als "grandfather rule" bezeichnen. Daher wird zwar In tierexperimentellen CPR-Untersuchungen konnte mit Vasopressin, dem in der HirnanhangsdrĂŒse gebildeten antidiuretischem Hormon, ein signifikant höherer linksventrikulĂ€rer myokardialer und zerebraler Blutfluss nachgewiesen werden als mit der maximal wirksamen Adrenalindosis [70,152]. Weiterhin war bei Schweinen das zerebrale Sauerstoffangebot mit Vasopressin höher als bei einer Reanimation mit Adrenalin [97].…”
Section: Adrenalin Oder Vasopressin Als Vasopressorunclassified